A Meta-analysis of the effect of functional dressing in nursing of pressure injury (功能性敷料在压力性损伤护理中应用效果的Meta分析) - WU Qian (吴倩); NING Yuyin (宁余音); BAI Zhiyu (柏志玉); HUANG Jie (黄洁); LU Junchen (陆俊辰); LIU Rui (刘芮); LIAO Zipeng (廖子鹏) (中西医结合护理)
Objective To explore the application effect of functional dressings in the nursing of pressure injuries, and to provide evidence-based basis for the nursing of pressure injuries. Methods Computer search for randomized controlled trials on the effects of functional dressings in nursing of pressure injury in the Cochrane Library, PubMed, WOS, CNKI, Wanfang Data and VIP databases, screened and included the literature, and the search time limit was from the establishment of the database to June 2020. Two reviewers independently conducted literature screening, data extraction, and quality evaluation in accordance with Cochrane quality evaluation standards, and then used RevMan 5. 3 software for Meta analysis. Results Totally 17 articles were included, with a total of 1206 patients. The results of Meta analysis showed that functional dressings were superior to the control group in terms of nursing satisfaction, healing status, and healing time except for the number of dressing changes (P<0. 05). Conclusion Compared with traditional dressings, functional dressings can reduce the number of dressing changes, shorten the healing time, increase the cure rate, and thus improve the patient's nursing satisfaction. It is a safe, economical and effective treatment method. (目的 探讨功能性敷料在压力性损伤护理中的应用效果, 为压力性损伤的护理提供循证依据。方法 计算机检索Cochrane Library、PubMed、WOS、中国知网、万方及维普数据库中关于功能性敷料对护理压力性损伤应用效果的随机对照试验, 筛检纳入文献, 检索时限为建库至2020年6月。由2名评价人员按照Cochrane质量评价标准独立进行文献筛选、资料提取和质量评价后, 采用RevMan 5. 3软件进行Meta分析。结果 纳入17篇文献, 共计1206例患者。Meta分析结果显示功能性敷料除换药次数外在护理满意度、愈合情况、愈合时间上均优于对照组(P＜0. 05)。结论 功能性敷料较传统敷料而言可以减少换药次数, 缩短愈合时间, 提高治愈率, 从而提升患者的护理满意度, 是一种安全、经济、有效的治疗方法。)